Screening of culture condition for xylanase production by filamentous fungi - Garcia Simoes, Maria Lucia; Tauk-Tornisielo, Samia Maria [UNESP]; Tapia Tapia, Daniel Mario (Academic Journals, 2009)
The objective of this research was to investigate xylanase production by filamentous fungi (Trichoderma viride) to determine the best cultivation conditions in the process, aiming toward optimization of enzyme production. The best temperature, as well as the best carbon source, for biomass production was determined through an automated turbidimetric method (Bioscreen-C). The enzyme activity of this fungus was separately evaluated in two solid substrates (wheat and soybean bran) and in Vogel medium, pure and by adding other carbon sources. Temperature effects, cultivation time, and spore concentrations were also tested. The best temperature and carbon source for enzyme and biomass production was 25 C and sorbitol, respectively. Maximum xylanase activity was achieved when the fungus was cultivated in wheat bran along with sorbitol (1%, w/v), using a spore concentration of 2 x 10(6) spores. mL(-1), pH 5.0, for 144 h cultivation. The study demonstrated not only the importance of the nature of the substrate in obtaining a system resistant to catabolic repression, but also the importance of the culture conditions for biosynthesis of this enzyme. T. viride showed a high potential for xylanase production under the conditions presented in these assays.
Keywords: Trichoderma viride; xylanase activity; enzyme optimization